UV Spectrophotometric Estimation of Acipimox inBulk and Capsule Dosage Form - A. Elphine Prabahar; B. Thangabalan; R. Kalaichelvi; P. Vijayaraj Kumar (E-Journal of Chemistry)
A new simple, rapid, accurate, sensitive and precise spectrophotometric method in ultra violet region has been developed for determination of acipimox (ACX) in bulk and capsule dosage form. Acipimox exhibited maximum absorbance at 231 nm with apparent molar absorptivity of 1.5104 × 104 in distilled water. Beer’s law was found to be obeyed in the concentration range 1-10 μg mL-1. Correlation coefficient was found to be 0.9998. The developed method was validated respect to linearity, precision, accuracy. The proposed method is useful for the routine estimation of ACX in bulk and capsule dosage form.